Analisis Kemampuan Berfikir Kritis Terhadap Permasalahan Produk Unggulan Kakao Pada Siswa Sekolah Menengah Atas Di Jember - Sudarti Sudarti; Lutfiana Ditta Sari; Rif’ati Dina Handayani (Postgraduate, University of Mataram, 2023)
The implementation of this research is limited by setting the problem of critical thinking skills to the problem of superior products in Jember, namely Cocoa students in Jember. This research was carried out using local wisdom on the subject matter of fermentation in cocoa beans. Students' thinking ability is carried out through filling in the work on test questions in the form of descriptions. The research will be carried out in October-November. The results of the research are the critical thinking skills of vocational students with a score of 76.53 higher than high school students with an average score of 62.37 for critical thinking skills. This shows that vocational students understand more about Jember's superior product, namely cocoa. Being in a district with one of the leading products, namely cocoa, makes vocational high School students equipped with knowledge about cocoa commodities, such as cocoa seeds, cocoa product development and cocoa processing methods. Thus, it is hoped that high school and vocational high school students will be able to make a maximum contribution in efforts to develop local products so that they can increase the progress and welfare of the local area. Problem-based learning that links learning materials and local wisdom is needed to support the improvement of students' critical thinking skills.